Evaluating Surveillance Measures at Airports in Responding to Airline Negligence and Lost Baggage - Lesmana, Sri Jaya; Lesmana, Reyhan Alifrinaldy; Indayatun, Ratna; Mofea, Sukhebi (Media of Law and Sharia, 2025)
Airport oversight in ensuring legal protection for passengers experiencing baggage loss due to airline negligence is a critical aspect of the aviation industry. This study aims to assess the effectiveness of supervision conducted by the Airport Authority Office in safeguarding passengers' rights in cases of baggage loss resulting from airline negligence. The research employs a normative-empirical legal method, utilizing both legal and conceptual approaches. The findings indicate that the oversight carried out by the First-Class Airport Authority (Otban) Region I at Soekarno-Hatta International Airport is generally effective and provides protection for passenger rights. However, the overall effectiveness of this supervision is highly dependent on consistent implementation and continuous improvement in passenger service quality. Ideal and effective airport oversight should encompass clear regulations, routine inspections, continuous monitoring, firm corrective measures, collaboration with relevant institutions, fair dispute resolution mechanisms, adequate training for officers, as well as transparency and accountability